1986
DOI: 10.1007/bf02412121
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bmax of [3H]-imipramine binding to platelets of depressed patients free of previous medication with 5HT uptake inhibitors

Abstract: The high-affinity binding sites for [3H]-imipramine (IMI) present in human platelets are associated with the neuronal uptake system for 5HT. It was recently demonstrated that previous antidepressant therapy with drugs which inhibit 5HT uptake could down-regulate [3H]-IMI binding and that this effect could persist up to 1 month after the end of treatment. We therefore re-examined the reported differences in Bmax of [3H]-IMI binding in platelets between control and depressed untreated patients, to evaluate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Another possible reason for finding low B, , values in depressed patients is the inclusion of patients treated with lithium, as long-term lithium treatment in rats has been found to reduce imipramine binding in rat brain (21) as well as several other receptors, dopamine (22), serotonin (23) and acetylcholine (24). However, very low B, , values in depressive patients who are guaranteed to be medication-free may also be seen in some patient populations, as reported in the recent study by Poirier et al (25). Our laboratory has also looked into this controversial matter.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Another possible reason for finding low B, , values in depressed patients is the inclusion of patients treated with lithium, as long-term lithium treatment in rats has been found to reduce imipramine binding in rat brain (21) as well as several other receptors, dopamine (22), serotonin (23) and acetylcholine (24). However, very low B, , values in depressive patients who are guaranteed to be medication-free may also be seen in some patient populations, as reported in the recent study by Poirier et al (25). Our laboratory has also looked into this controversial matter.…”
Section: Discussionsupporting
confidence: 53%
“…Both differences and no differences in B, , between depressed patients and control persons have been published (Table l), but a majority of studies find a decrease in B,,,,. However, very low B, , values in depressive patients who are guaranteed to be medication-free may also be seen in some patient populations, as reported in the recent study by Poirier et al (25). Recently it has been found that chlorimipramine (AnafraniP) treatment reduces imipramine binding (18,19) and that the effect lasts several weeks after discontinuation of the treatment (20).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, if L3H1imipramine were labeling the serotonin transporter, changes in the V, , for uptake should be paralleled by changes in B, , for binding. Poirier et al (1986) did detect this relationship, with reduced r3H]imiprarnine binding in depressed patients that normalized after ADT. Similar results were obtained by Wagner et al (1987).…”
Section: L3h]imipramine Binding To Plateletsmentioning
confidence: 88%
“…During theRast few years, a significant decrease in the density of platelet H-imipramine binding sites (Bmax) in untreated depressed patients as compared with sex-matched and agematched healthy controls has been reported by a number of authors (Briley et al, 1980;Raisman et al, 1981;Wood et al, 1983;Suranyi-Cadotteet al, 1985), although this was not con-fmned by some others (Mellerupet al, 1982;Whitakeret al, 1984). This decrease does not seem to be a residual effect of previous antidepressant medication (Poirier et al, 1986), and has been found to be reversible after full c1inical improvement induced by treatment with tricyclic antidepressants (Suranyi-Cadotte et al, 1985) or electroconvulsive therapy (Langer et al, 1986). It has been regarded, therefore, as a possible state-dependent biological marker of depression.…”
Section: Introductionmentioning
confidence: 98%